Juridical Review of Journalist Who Were Victims of Violence by Unknown Persons During the Coverage of Demonstrations - Benaya Milionhart; Aristoteles; Rizki Setyobowo Sangalang (Dinasti Research, 2025)
Security and legal protection for journalists, as a profession that plays an important role in conveying information to the public, is a crucial aspect that requires serious attention. The phenomenon of violence against journalists who are victims while covering demonstrations is increasingly occurring, both at the global level and in Indonesia. Diverse public perceptions of demonstrations often put journalists in vulnerable positions, where they are perceived as a threat by certain parties. Violence committed by unknown persons is a serious challenge because perpetrators are often difficult to identify or identify. This situation is further complicated when the perpetrators destroy evidence that can be used to reveal their identities. This study aims to find out the legal arrangements and protection for journalists who are victims of acts of physical and psychological violence by unknown perpetrators. The approach used is normative juridical, utilizing case analysis, historical approaches, and legal sociology, as well as literature reviews from reliable sources. The findings of the study show that legal protection for journalists in cases of violence during reporting on demonstrations is still not optimal. Weaknesses in existing legal arrangements are significant challenges that need to be addressed immediately to ensure the security and protection of the rights of journalists in carrying out their duties.